2022
DOI: 10.3390/ijms23169036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Modulating Effect of Anthocyanin-Rich Sour Cherry Extract on Occludin and ZO-1 on Caco-2 and HUVEC Cultures

Abstract: Increased permeability of the epithelial and endothelial cell layers results in the onset of pathogenic mechanisms. In both cell types, cell–cell connections play a regulatory role in altering membrane permeability. The aim of this study was to investigate the modulating effect of anthocyanin-rich extract (AC) on TJ proteins in inflammatory Caco-2 and HUVEC monolayers. Distribution of Occludin and zonula occludens-1 (ZO-1) were investigated by immunohistochemical staining and the protein levels were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The integrity of the monolayer is a vital factor for transport studies, especially when the passive transport of drug or formulation through tight junctions can be expected. To check the high confluency, besides confocal microscopy, fluorescently-labeled markers such as fluorescein [33,37], lucifer yellow [38], or radiolabeled markers like C 14 mannitol [24] are used. Additionally, the transepithelial electrical resistance (TEER) should be monitored on a regular basis using a volt-ohmmeter equipped with a "chopstick" electrode [38,39].…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations
“…The integrity of the monolayer is a vital factor for transport studies, especially when the passive transport of drug or formulation through tight junctions can be expected. To check the high confluency, besides confocal microscopy, fluorescently-labeled markers such as fluorescein [33,37], lucifer yellow [38], or radiolabeled markers like C 14 mannitol [24] are used. Additionally, the transepithelial electrical resistance (TEER) should be monitored on a regular basis using a volt-ohmmeter equipped with a "chopstick" electrode [38,39].…”
Section: Cell Culturementioning
confidence: 99%
“…To check the high confluency, besides confocal microscopy, fluorescently-labeled markers such as fluorescein [33,37], lucifer yellow [38], or radiolabeled markers like C 14 mannitol [24] are used. Additionally, the transepithelial electrical resistance (TEER) should be monitored on a regular basis using a volt-ohmmeter equipped with a "chopstick" electrode [38,39]. The integrity of the Caco-2 monolayer can be considered sufficient if the TEER values are at least 800-900 Ω cm 2 [35,36].…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that polyphenols possess anti-inflammatory effects and vasorelaxation activity due to the suppression of the release of pro-inflammatory mediators [ 16 , 17 , 18 ]. We have also recently published several studies that investigated the relationship between the inflammation-induced HUVEC model and bioflavonoids, primarily anthocyanins [ 19 , 20 ]. Flavonoids are phenolic compounds which are found in plants, vegetables and fungi as secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%